Investigating the Sri Lankan Cassava Mosaic Disease-related Characteristics of Cassava (Manihot esculenta Crantz) - Nomura, Hisako; Baba, Tamon; Khin, Sophary; Pok, Panha; Than, Tha; Kim, Ok-Kyung; Natsuaki, Keiko; Srean, Pao; Ito, Kasumi (Badan Penerbitan Fakultas Pertanian (BPFP), 2024)
In this study, we aimed to investigate which components of cassava (Manihot esculenta Crantz) would be associated with the cassava tuber weight when infected with the Sri Lankan Cassava Mosaic Virus (SLCMV). We conducted multiple regressions to find associations between other cassava elements and tuber weights. This study was carried out in the Rukhak Kiri district in Battambang Province, located in northwestern Cambodia, in March 2019. We assessed two major varieties used in the region, namely, KU 50 and Rayong 7, using 90 samples—60 samples of KU 50 and 30 samples of Rayong 7. The results showed that the tuber weight of KU 50 was heavier than that of Rayong 7. In addition, the biomass of the stem, that is, the weight of all branches and leaves, were the sole strong factors associated with tuber weight for both KU 50 and Rayong 7. Moreover, as the tuber number declined, the tuber weight declined rapidly for Rayong 7. Overall, we concluded that SLCMV infection affects the biomass weight of cassava.